Implementing a triage tool to improve appropriateness of care for children coming to the emergency department in a small hospital in India. Issue 4 (12th October 2020) - Joshi, Neha; Wadhwani, Rakhi; Nagpal, Jitender; Bhartia, Saru
Abstract : Background: In 2015, senior consultants at Sitaram Bhartia Institute of Science and Research saw several sick children in their outpatient clinics for which they had been seen in the emergency department the previous day. These children seemed to require admission but were sent home. This prompted us to review the paediatric care provided in our emergency department. Methods: A multidisciplinary team was formed to run this improvement initiative. Review of literature suggested that establishing a triage system around a prevalidated triage tool would help us deliver more appropriate care. The South African Triage Scale was selected and adapted. Interventions: With the aim of delivering appropriate care to at least 50% of children, a series of sequential interventions were tested using the improvement methodology of Plan-Do-Study-Act (PDSA) cycles, an approach recommended by the Institute for Healthcare Improvement. Learnings from the PDSA cycle of the previous intervention helped decide the subsequent change idea. The interventions included training in use of tool, increasing nurse staffing levels, using team huddles as feedback opportunities, introducing nurse reminders, reducing non-productive work, developing local leadership and training a restricted group of locum paediatricians. Qualitative and quantitative information was analysed to retain or reject change ideas. Results: At baseline only 16%–17% of children were receiving appropriate care. The sequential changes resulted in a gradual improvement to a median of 63% of children receiving appropriate care by the end of 20 months. Conclusions: We succeeded in establishing a paediatric emergency triage system and culture in the given setting through a unique enriching experience. We worked on removing systemic barriers and facilitating change while facing several unexpected outcomes. A sustained iterative approach may be the best way to achieving significant improvement in difficult settings like ours.